2012
DOI: 10.1007/s00259-012-2292-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between stress myocardial perfusion SPECT recorded with cadmium-zinc-telluride and Anger cameras in various study protocols

Abstract: Concordance between the results of CZT and Anger SPECT is good regardless of study protocol and especially when excluding obese patients who have low-count Anger SPECT and for whom myocardial counts are dramatically enhanced on CZT SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 27 publications
2
18
0
2
Order By: Relevance
“…12 The resulting level of the corresponding parameter is hence around 100-fold lower than that of the actual sensitivity. 13 Among all commercially available gamma-cameras, the D.SPECT CZT camera is the model showing the highest tomographic count sensitivity, although no more than 1% of the emitted photons are actually recorded by this camera on cardiac phantoms. This percentage is twofold lower for the Discovery CZT camera, and 7-to 8-fold lower for conventional Anger cameras.…”
Section: See Related Article Pp 885-893mentioning
confidence: 99%
“…12 The resulting level of the corresponding parameter is hence around 100-fold lower than that of the actual sensitivity. 13 Among all commercially available gamma-cameras, the D.SPECT CZT camera is the model showing the highest tomographic count sensitivity, although no more than 1% of the emitted photons are actually recorded by this camera on cardiac phantoms. This percentage is twofold lower for the Discovery CZT camera, and 7-to 8-fold lower for conventional Anger cameras.…”
Section: See Related Article Pp 885-893mentioning
confidence: 99%
“…These cameras allow for reduced imaging time (5) and reduced exposure of patients to radiation (6,7) but are not equivalent in terms of count sensitivity and spatial resolution, leading to images with differences in sharpness and contrast-to-noise ratio in clinical practice (8). Previous publications have validated the performance and results of these cameras versus the conventional Anger camera in clinical practice (9,10), but recent data demonstrated that when quantitative gated SPECT is performed using CZT cameras instead of Anger cameras, LV volume is overestimated, leading to a lower estimated LVEF in healthy patients (11). This difference is likely related to the increased spatial resolution, a condition that also significantly affects the assessment of segmental wall motion and thickening (12,13).…”
mentioning
confidence: 99%
“…Combined with a stationary array of pinhole detectors focused on the heart, resulting in a threefoldto-fourfold increase in SPECT volume sensitivity, 12 this allows for the opportunity to lower injected activity (patient dose) without sacrificing image quality. [13][14][15] Previous studies have shown good concordance with existing SPECT technology 16,17 and coronary angiography, 12,18 with some evidence of superiority in the obese 16 due to increased counts; examinations of prognostic value have demonstrated an association between all-cause mortality and total perfusion abnormality. 19 We therefore hypothesized that CZT and conventional cameras would prognosticate equally, given differences in baseline clinical characteristics.…”
Section: Introductionmentioning
confidence: 94%